Knowledge, Awareness and Attitude Related to First Aid among Iium Kuantan Campus Students - Thandar Soe, Sumaiyah Jamaludin @; Zakaria, Muhammad Allif Bin (IIUM Medical Journal Malaysia, 2017)
Introduction: Accidental injuries are one of the leading causes of morbidity and mortality worldwide. Approximately 1.25 million lives are cut short because of road traffic accident every year. As the incidences of emergencies is steadily increasing in recent years, it is important to ensure that individuals are adequately trained to deal with such events including university students. First aid is given to preserve life and minimize the consequences of injury and illness until help is obtained from health care practitioners. This study aimed to assess the level of knowledge, awareness and attitude related to first aid among IIUM Kuantan campus students. Materials and method: A quantitative cross-sectional survey with stratified random sampling was conducted among 348 IIUM Kuantan undergraduate students who met the study inclusion criteria. Data were collected by using the self-administered questionnaire which was adapted from Hong Kong Red Cross. Results: A total of 316 participants had positive awareness and attitude towards first aid knowledge. Nevertheless, 149 participants had moderate level of first aid knowledge. There were significant associations (p value of 0.05) between gender, faculty, year of study, and first aid training experience and their level of first aid knowledge. However, 55.4% of study participants did not have experience in taking first aid course and they have little knowledge on first aid. Conclusion: Although the majority of participants had positive awareness and attitude towards first aid, their knowledge and experience in taking first aid course were unsatisfactory. Therefore, there is a need of proper and regular educational programs to raise awareness in the student community about the importance of first aid.